Understanding the variability in rotational traction testing on artificial turf - McGowan, H.; Fleming, P.; James, D.; Forrester, S. (Sports Engineering, 2023)
Rotational traction is a key parameter used by sporting governing bodies to determine the safety and performance of artificial turf surfaces. Currently, the Federation Internationale de Football uses two devices for measuring rotational traction: a statically loaded rotational traction tester and a lightweight rotational traction tester, loaded by the operator. Variability in measurements emanates from two main sources: inconsistencies in the turf and the manual operation of both testers. The purpose of this study was to investigate the contributions from the turf and the manual operation of the testers to the total variability in peak torque measurements, achieved by comparing results from both manually operated rotational traction testers with an automated rotational traction tester. Five experienced operators used the manual testers to conduct 15 rotational traction tests on four different artificial turf surfaces. The automated tester measured rotational traction on each surface 15 times. The results revealed the turf system contributed over 50% of the total variability for both manually operated testers, on all four surfaces. The lightweight tester produced greater between (inter)-operator variability, but lower within (intra)-operator variability compared to the standard rotational traction tester. Operator height appeared to influence results for the lightweight tester, but not for the standard tester. The results support the continued use of manual rotational traction testers for commercial compliance field testing of artificial turf surfaces; however, they indicate the need to further explore the effects of manual operation on both devices.